Pengaruh Teknologi Informasi dan Risiko Bisnis Pada Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Selama Pandemi Covid-19 di Kota Denpasar - Ni Wayan Yuniasih; Putu Deddy Samtika Putra; Sang Ayu Putu Arie Indraswarawati; I Putu Edi Saputra; Ni Kadek Sukma Intan Cahyani (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The Covid-19 pandemic has had a major impact on the MSME sector. Business owners are faced with operational changes by taking advantage of technological advances and anticipating business risks. This study aims to determine the effect of information technology and business risk on MSME development. This research was conducted on SMEs in Denpasar City. The research sample used probability random sampling by taking 100 respondents as a sample. Research data was collected through distributing questionnaires. The research hypothesis was tested with multiple regression analysis. The results of the study show that information technology and business risk have a positive effect on MSME development. Entrepreneurs who are able to take advantage of technological advances and have good risk management will grow their business faster.